1988
DOI: 10.1063/1.455047
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism of oriented α helices. I. Proof of the exciton theory

Abstract: Moffitt’s exciton theory for α helices, an important cornerstone of the circular dichroism (CD) theory for biopolymers, was recently cast in doubt by a linear dichroism measurement of electric field oriented polypeptides [Yamaoka et al., J. Am Chem. Soc. 108, 4619 (1986)]. In particular the prediction that the polarization of an exciton split component at 208 nm should be parallel to the α-helical axis was not borne out. This revealed the inadequacy of previous experiments which used long polypeptides to prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 29 publications
3
90
0
Order By: Relevance
“…Our data imply that self-assembly of DCD-1L can lead to the formation of ion channels, with a diameter similar to or even smaller than the barrel-stave model of CAMPs (43). Several studies have previously shown that peptide self-assembly in the membrane-bound state correlates with antimicrobial activity (30), whereas complex formation in an aqueous environment had no effect on antimicrobial activity (44).…”
Section: Discussionmentioning
confidence: 73%
“…Our data imply that self-assembly of DCD-1L can lead to the formation of ion channels, with a diameter similar to or even smaller than the barrel-stave model of CAMPs (43). Several studies have previously shown that peptide self-assembly in the membrane-bound state correlates with antimicrobial activity (30), whereas complex formation in an aqueous environment had no effect on antimicrobial activity (44).…”
Section: Discussionmentioning
confidence: 73%
“…OCD has been successfully used to study the physical state of the peptides embedded in phospholipid bilayers. OCD determines not only the secondary structure of a peptide but also its orientation in membranes (15,16). The ease of OCD measurement makes it a very effective method for probing the peptide orientation in membranes, particularly if the orientation changes with membrane conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For most experiments as in this one, normal (rather than oblique) incidence OCD is sufficient for the orientation analysis (16). OCD has been used to determine the orientation of various helical peptides including alamethicin (15)(16)(17)27), magainin (28), melittin (29) and synthetic helices (30), -sheet peptides protegrins (31), and cyclic peptides θ-defensins (32). LPS bilayers have a strong OCD.…”
Section: Materials Lps Frommentioning
confidence: 99%
See 2 more Smart Citations